Prevalência de ectoparasitos em caprinos e ovinos do município de Mossoró, Rio Grande do Norte - Bezerra, Ana Carla Diógenes Suassuna (2007)
significant loss in the productive of the flock. Have been examined 15 establishments of reform agrarian in the period between august 2005 at november 2006, with objective of identify ectoparasites the of goat and sheep. After the animal s exam, was proceeded the scraped, exam direct of fur and collect of pavilion headphone. Of the 494 goat inspect, 89.87% had positive, while 76.72% sheep. The arthropods identified in goat was: Damalinia caprae (89.87%), Rhipicephalus microplus (1.01%), furthermore, the larvae of Cochliomyia hominivorax (0.4%), Psoroptes cuniculi (0.4%), and Ctenocephalides felis (3.23%), Amblyomma parvum (1.01%) and Linognathus stenopsis (0.2%), that for the first time examine this specie within of the Nordeste s brasilian. And several multiparasitism of the D. caprae with R. microplus (0.46%) and P. cuniculi with D. caprae (0.23%). In sheep D. caprae with R. microplus (0.46%)p was found D. ovis (74.5%), R. microplus (0.86%), larvae of C. hominivorax (0.43%) and A. parvum (0.43%) was resisted in fist time, into species, within of the region Nordeste s Brazil being added, the association of D. ovis with R. microplus (0.56%). In relation to the sex and old animals, haven t association (p>0.05). In roll to the period year, have difference (p<0.05), with epoch drought to demonstrating big prevalence (82.15%). To return important the development of studies to evaluate your important as factor limit for production animals